2020
DOI: 10.1212/nxi.0000000000000741
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré syndrome related to COVID-19 infection

Abstract: Autoimmune diseases following collection(s): This article, along with others on similar topics, appears in the Permissions & Licensing http://nn.neurology.org/misc/about.xhtml#permissions its entirety can be found online at: Information about reproducing this article in parts (figures,tables) or in Reprints http://nn.neurology.org/misc/addir.xhtml#reprintsus Information about ordering reprints can be found online: Academy of Neurology.. All rights reserved. Online

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
336
1
35

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 335 publications
(381 citation statements)
references
References 8 publications
9
336
1
35
Order By: Relevance
“…5,7,9 Reports are now emerging of similar associations with COVID-19 and GBS, and with GBS variants, including the Miller-Fisher syndrome. [41][42][43][44][45][46] The largest series to date, describes five patients. 47 In this series, all patients developed GBS 5 to 10 days following COVID-19 symptom onset.…”
Section: Post-infectious and Immune-mediated Complications Of Sars-cov-2mentioning
confidence: 99%
“…5,7,9 Reports are now emerging of similar associations with COVID-19 and GBS, and with GBS variants, including the Miller-Fisher syndrome. [41][42][43][44][45][46] The largest series to date, describes five patients. 47 In this series, all patients developed GBS 5 to 10 days following COVID-19 symptom onset.…”
Section: Post-infectious and Immune-mediated Complications Of Sars-cov-2mentioning
confidence: 99%
“…A total of 18 patients reported in 14 papers [12][13][14][15][16][17][18][19][20][21][22][23][24][25] were included in this review. The 14 selected papers consisted of 13 case reports and one series.…”
Section: Study Selectionmentioning
confidence: 99%
“…Table 4 shows the diagnostic ancillary tests, outcome and treatment. Fourteen cases were from Europe [12,[16][17][18][19][20][22][23][24][25], one from the USA [13], one from China [14], one from Iran [15] and one from Morocco [21]. Ten patients were males whilst eight were females.…”
Section: Study Selectionmentioning
confidence: 99%
“…GBS occurred in 5/1200 (0.4%) patients with COVID-19 in one of the studies [13]. There were six other case report of GBS, one Miller Fisher syndrome, and two polyneuritis cranialis [14,[24][25][26][27][28][29][30]. Interestingly, neurotropism of human coronaviruses has been suggested by in vitro and in vivo studies that showed that certain strains of the viruses could persist in the human CNS by targeting oligodendrocytic and neuroglial cell lines [41].…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-one patients experienced a cerebrovascular complication, with 27 ischemic strokes [11,[19][20][21][22][23], 3 hemorrhagic strokes [11,15,23] and 1 cerebral venous sinus thrombosis [11]. There were 15 patients with GBS [13,14,[24][25][26][27][28][29][30] or its variants, 6 reported as encephalitis [12,18,[31][32][33], one with seizures [34], one with acute hemorrhagic necrotizing encephalopathy [16] one reported as transverse myelitis [35], and one reported as ADEM [36]. Nine of these cases were reported as fatal.…”
mentioning
confidence: 99%